Fluorescent colors in orchid bees (Hymenoptera: Apidae) - Nemésio,André (2005)
The presence of UV-fluorescent pigments is described for the first time in insects. The clear hairs on terga I, III and IV of Eulaema niveofasciata (Friese) are the only ones among several Euglossina species which fluoresce, supporting recent taxonomic studies which suggested that this endemic species of the Atlantic Forest domain and Eulaema bombiformis (Packard) are really different species. The UV-color pattern may have effects both on mating behavior and warning to predators.